At the threshold of the Fourth Industrial Revolution: Who Gets Who Loses - Kraftová, Ivana; Doudová, Iveta; Miláček, Radim (My University, 2018)
At the beginning of the second decade of the 21st century, the fourth industrial revolution based on the digitization of production processes, more precisely connecting the virtual world to the real world began. The aim of this article is to present the results of the research that focused on comparing the positions of the selected group of countries at the threshold of the fourth industrial revolution in terms of their performance and competitiveness. The analysis is aimed at 13 countries - the six largest economies of the world and seven economies of the former Soviet bloc - from 1993 to 2015 using the localization quotient and index of regional concentration of the sector on the basis of added value, supplemented by the SHADE model, using the Balassa index and evaluating the comparative advantage of countries in the area of ICT. The research defines the positioning formulas of countries for the manufacturing and ICT industries. It cannot be said that the differences in localization, or rather the concentration of the sectors surveyed were determined by the size of the economy or its membership of traditional market economies. Exportability in ICT goods positively evaluates those economies that have managed to increase their positive Balassa index over time, or rather to get from its negative values to positive ones. The beginning of the fourth industrial revolution is an unrepeatable moment of human history, just as it was with the first, second and third industrial revolutions. The one who knows and is able to accept, use and multiply the supporting trends is the one who gains.
Na prahu čtvrté průmyslové revoluce: kdo získává, kdo ztrácí
Keywords: the Fourth Industrial Revolution; localization and concentration of industry; manufacturing; ICT; position pattern; ICT goods; comparative advantage; performance; competitiveness; čtvrtá průmyslová revoluce; lokalizace a koncentrace odvětví; průmysl; ICT; vzory chování; zboží ICT; komparativní výhoda; výkonnost; konkurenceschopnost